Indoor Air Quality In Adaptively Reused Heritage Buildings At A Unesco World Heritage Site, Penang, Malaysia - Prihatmanti, Rani; Bahauddin, Azizi (Penerbit Universiti Sains Malaysia, 2014)
This study investigated the Indoor Air Quality (IAQ) level in heritage buildings that have been adaptively reused as office buildings. These buildings are located within the vicinity of the UNESCO World Heritage Site in George Town, Penang. The aim of this study was to determine the IAQ level in the designated buildings using thermal monitoring and chemical and microbial tests. Mixed methods were used in this cross-sectional study to achieve the objectives. The IAQ tests variables were the temperature, relative humidity, air velocity, airborne pollutants (Particle Matter 10 [PM10], carbon monoxide, carbon dioxide and formaldehyde), total bacteria count and total fungal count. These variables were adopted from the Industry Code of Practice on Indoor Air Quality, Department of Occupational Health Malaysia and the Malaysian Green Building Index–Non Residential Existing Building (NREB) rating tool. The measurements show that the IAQ level in the identified buildings was unacceptable within the standards stipulated. Dampness stains and mould were present in all buildings due to high humidity and moisture levels. It can be concluded that the IAQ level was due to inappropriate adaptive reuse practices, the occupants' activities and maintenance irregularities.